2010
DOI: 10.4103/0971-9784.58829
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an adjunct to anesthetic induction to attenuate hemodynamic response to endotracheal intubation in patients undergoing fast-track CABG

Abstract: During induction of general anesthesia hypertension and tachycardia caused by tracheal intubation may lead to cardiac ischemia and arrhythmias. In this prospective, randomized study, dexmedetomidine has been used to attenuate the hemodynamic response to endotracheal intubation with low dose fentanyl and etomidate in patients undergoing myocardial revascularization receiving beta blocker treatment. Thirty patients undergoing myocardial revascularization received in a double blind manner, either a saline placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 26 publications
(36 reference statements)
2
59
0
Order By: Relevance
“…Mariappan et al showed similar hemodynamic profiles when they compared oral clonidine premedication and perioperative dexmedetomidine infusion [23]. Most studies showed that, compared to saline, dexmedetomidine as a premedication significantly decreased hypertensive and tachycardia responses that occur due to intubation [8, 2426]. Becker et al reported that the dexmedetomidine infusion after intubation in craniotomy patients resulted in fewer antihypertensive requirements [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mariappan et al showed similar hemodynamic profiles when they compared oral clonidine premedication and perioperative dexmedetomidine infusion [23]. Most studies showed that, compared to saline, dexmedetomidine as a premedication significantly decreased hypertensive and tachycardia responses that occur due to intubation [8, 2426]. Becker et al reported that the dexmedetomidine infusion after intubation in craniotomy patients resulted in fewer antihypertensive requirements [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a limited number of studies have evaluated the usage of dexmedetomidine [7, 8]. Dexmedetomidine is 1600 times more selective to α-2 receptors than to α-1 receptors (clonidine, 200:1), and this high selectivity contributes to increases in hypnotic and analgesic efficacies and decreases in cardiovascular side effects [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they measured catecholamine concentration and found that the concentration of noradrenaline in mixed venous plasma was smaller in the dexmedetomidine group during all phases of induction. Ferdi Menda et al .,[17] concluded that dexmedetomidine effectively blunts the hemodynamic response to endotracheal intubation in patients undergoing myocardial re-vascularization and can be safely used at induction of general anesthesia in combination with fentanyl even among patients receiving beta blockers.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of α-2 agonists in decreasing the MAC for volatile anesthetics and opioids have been previously reported[17] and possibly is mediated through both pre- and post-synaptic α-receptor activation in the central nervous system. [1819] Reports available in the literature have reported use of dexmedetomidine as an adjunct to general anesthesia. When administered as a premedication at a dose range of 0.33-0.67 μg/kg given 15 min before surgery, it appears to be efficacious while minimizing the cardiovascular side-effects of hypotension and bradycardia.…”
Section: Discussionmentioning
confidence: 99%